SEASONAL DISAPPEARANCE OF FAR-INFRARED HAZE IN TITAN'S STRATOSPHERE - Jennings, D; Anderson, C; Samuelson, R; Flasar, F; Nixon, C; Kunde, V; Achterberg, R; Cottini, V; de Kok, R; Coustenis, A; Vinatier, S; Calcutt, S (2012)
A far-infrared emission band attributed to volatile or refractory haze in Titan's stratosphere has been decreasing in intensity since Cassini's arrival in 2004. The 220cm-1 feature, first seen by the Voyager Infrared Interferometer Spectrometer, has only been found in Titan's winter polar region. The emission peaks at about 140km altitude near the winter stratospheric temperature minimum. Observations recorded over the period 2004-2012 by the Composite Infrared Spectrometer on Cassini show a decrease in the intensity of this feature by about a factor of four. Possible seasonal causes of this decline are an increase in photolytic destruction of source chemicals at high altitude, a lessening of condensation as solar heating increased, or a weakening of downwelling of vapors. As of early 2012, the 220cm-1 haze has not yet been detected in the south. The haze composition is unknown, but its decrease is similar to that of HC3N gas in Titan's polar stratosphere, pointing to a nitrile origin. © 2012. The American Astronomical Society. All rights reserved.